Mindfulness Meditation Is Related to Long-Lasting Changes in Hippocampal Functional Topology during Resting State: A Magnetoencephalography Study. (18th December 2018) - Lardone, Anna; Liparoti, Marianna; Sorrentino, Pierpaolo; Rucco, Rosaria; Jacini, Francesca; Polverino, Arianna; Minino, Roberta; Pesoli, Matteo; Baselice, Fabio; Sorriso, Antonietta; Ferraioli, Giampaolo; Sorrentino, Giuseppe; et al.
Abstract : It has been suggested that the practice of meditation is associated to neuroplasticity phenomena, reducing age-related brain degeneration and improving cognitive functions. Neuroimaging studies have shown that the brain connectivity changes in meditators. In the present work, we aim to describe the possible long-term effects of meditation on the brain networks. To this aim, we used magnetoencephalography to study functional resting-state brain networks in Vipassana meditators. We observed topological modifications in the brain network in meditators compared to controls. More specifically, in the theta band, the meditators showed statistically significant (p corrected = 0.009) higher degree (a centrality index that represents the number of connections incident upon a given node) in the right hippocampus as compared to controls. Taking into account the role of the hippocampus in memory processes, and in the pathophysiology of Alzheimer's disease, meditation might have a potential role in a panel of preventive strategies.